Komponen Kimia dan Anatomi Tiga Jenis Bambu dari Seram, Maluku - Mery Loiwatu; Elyazar Manuhuwa (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2008)
As a versatile plant, the basic properties of bamboo are various, depending on species, site, and position inside the stem. This study was conducted at three sites (Buria, Morekao, Tala), on three species (Dendrocalamus asper, Schizos- tachyium brachycladum, Schyzotachium lima), and three positions of the stem (base, middle, top). Objective of the study was to measure chemical component and anatomical feature of the three species of bamboos of West Ceram’s Sub-district (Taniwel, Piru, Kairatu) and three parts of stem (base, middle, top). Factorial experiment in split plot design was applied in the study with 3 replications. Result of the study indicated that there was a significant effect of location on the lignin content, diameter of the fiber and fiber cells lumen, and proportion of parenchyma cells; species of bamboo to the length and diameter of fiber cells; and portion of stem to the extractive soluble in hot water, soluble in alcohol benzene, length and diameter of fiber cells, and diameter of fiber lumens. Extractive soluble in cold water was 3.10-3.79 %; hot water was 5.43-6.23 %; alcohol benzene was 3.37-4.10 %; alpha cellulose was 44.22-46,94 %; holocellulose was 71.97-75.57 %; lignin was 26.00-27.37 %; length of fiber cell was 3.40-3,96 mm; diameter of fiber cell was 4.34-4.91 micron; diameter of fiber cell lumens was 2.74-3.23 micron; cell wall thickness of fiber cell was0.76-0.91 micron; proportion of parenchyma cells was 51.95-56.85 %; proportion of fiber cells was 27.81-62.66 %;and proportion of pores was 12.39-14.60 %.ABSTRAKSebagai tanaman serbaguna, sifat dasar bambu bervariasi menurut jenis, tempat tumbuh dan posisi didalam batang. Penelitian dilakukan pada 3 lokasi (Buria, Morekao, Tala), terhadap 3 jenis bambu (Dendrocalamus asper, Schizos- tachyium brachycladum, Schyzotachium lima), dan 3 posisi dalam batang (pangkal, tengah dan ujung). Tujuan pene- litian adalah untuk mengukur komponen kimia dan anatomi 3 jenis bambu (Dendrocalamus asper, Schizostachyium brachycladum, Schyzotachium lima) asal 3 kecamatan Seram bagian barat (Taniwel, Piru, Kairatu), dan 3 bagian batang (pangkal, tengah dan ujung). Percobaan faktorial dalam rancangan petak terpisah digunakan dalam penelitian dengan 3 ulangan. Hasil penelitian menunjukkan pengaruh signifikan lokasi terhadap kadar lignin, diameter sel serat dan rongga sel serat dan proporsi sel parensim; jenis bambu terhadap panjang dan diameter sel serat; posisi dalam batang terhadap kadar ekstraktif larut air dingin, ekstraktif larut alkohol benzen, panjang dan diameter sel serat, dan diameter sel serat. Ekstraktif larut air dingin berkisar 3,10-3,79 %; larut air panas 5,43-6,23 %; larut alkohol benzen3,37-4,10 %; alfa selulosa 44,22-46,94 %; holoselulosa 71,97-75,57 %; lignin 26,00-27,37 %; panjang sel serat 3,40-3,96 mm; diameter sel serat 4,34-4,91 mikron; diameter rongga sel serat 2,74-3,23 mikron; tebal dinding sel serat0,76-0,91 mikron proporsi sel parensim 51,95-56,85 %; proporsi sel sel serat 27,81-62,66 %; dan proporsi sel pori12,39-14,60 %.